The role of cellular prion protein in Alzheimer’s disease - Correia, Ângela Patricia da Silva (2016)
Alzheimer’s disease (AD) is the most prevalent age-related neurodegenerative disease that leads to cognitive impairment and dementia. The major defined pathological hallmark of AD is the accumulation of amyloid beta (Aβ), a neurotoxic peptide, derived from beta and gamma-secretase cleavage of the amyloid precursor protein (APP). It has been described that cellular prion protein (PrPC) plays a role in the pathogenesis of Alzheimer disease. Although, the role of PrPC is still unclear, previous studies showed contradictious results. To elucidate this issue, the main objective of the present study is to investigate the influence of a knockout of the PRNP gene in 5XFAD mice, 5xFAD mice exhibited 5 mutations related to familial Alzheimer disease. These mice show an Aβ1-42 accumulation and an increased neuronal loss during aging. To create a bi-transgenic 5xFAD mice were crossed with Prnp0/0 Zurich 1 mice (prion protein knockout mice). We subjected two transgenic mice (5xFAD and Prnp0/05xFAD) at different ages (3, 9 and 12 months of age) to a battery of task to evaluate cognitive and motoric deficits and a biochemical analysis (ELISA, western blot and immunohistochemistry) to investigate the regulation and potential involvement of downstream signaling proteins in the Aβ induced toxicity process dependent of the PrPC concentration. The study revealed that the deficits induced by Aβ mediated toxicity appeared earlier in 5xFAD mice (9 months of age) than in Prnp0/05xFAD (12 months of age). Investigating the amount of amyloid beta in 5xFAD mice we observed a PrPC dependent regulation in 9 month-old animals of Aβ1−40 but not of the toxic form Aβ1−42. We did not found in Prnp0/05xFAD mice the up-regulation of P-Fyn, Fyn or Cav-1 as we found in 5xFAD mice. This suggests an important role of PrPC in Alzheimer’s disease as a promoter of toxic effect of Aβ oligomers. Our results may suggest the loss of PrPC delays the toxicity of amyloid beta. In conclusion, our data support a role of PrPC as a mediator of Aβ toxicity in AD by promoting early onset of disease.